Extraction of Diterpene-Phytochemicals in Raw and Roasted Coffee Beans and Beverage Preparations and Their Relationship - Fábio Junior Moreira Novaes; Maria Alice Esteves da Silva; Diana Cardoso Silva; Francisco Radler de Aquino Neto; Claudia Moraes Rezende (Plants, 2023)
Cafestol and kahweol are expressive furane-diterpenoids from the lipid fraction of coffee beans with relevant pharmacological properties for human health. Due to their thermolability, they suffer degradation during roasting, whose products are poorly studied regarding their identity and content in the roasted coffee beans and beverages. This article describes the extraction of these diterpenes, from the raw bean to coffee beverages, identifying them and understanding the kinetics of formation and degradation in roasting (light, medium and dark roasts) as the extraction rate for different beverages of coffee (filtered, Moka, French press, Turkish and boiled). Sixteen compounds were identified as degradation products, ten derived from kahweol and six from cafestol, produced by oxidation and inter and intramolecular elimination reactions, with the roasting degree (relationship between time and temperature) being the main factor for thermodegradation and the way of preparing the beverage responsible for the content of these substances in them.